ICT utilization by private higher learning institutions in Kedah, Penang and Perak: an analytical study in department offering business and management courses / Khairul Adilah Ahmad ... [et al.] - Ahmad, Khairul Adilah; Wan Salleh, Wan Zulkipli; Ahmad, Rosidah (2007)
This study examines the extent and utilization of ICT usage among private higher learning institutions in Kedah, Penang and Perak. Its focus is on (a) the purpose and patterns of ICT usage, with focus on the Internet, the ICT resources available for academic staff and to what extend do the lecturers used the ICT facilities available at their institutions. It will also look into the training regarding ICT that are in demand among lecturers to upgrade their knowledge in ICT. The software used to analyze the data is SPSS v. 12.0.1. From the finding, we discovered that the utilization of ICT among educators relies heavily on the extensiveness of computer resources availability at their premises. The educators also fairly strong agree that ICT is a valuable instructional tool and by utilizing it in their preparing for teaching materials and in class teaching will enhance their professional development. The main purpose for ICT use is for computer included information retrieval, creating teaching materials, email and word processing. The result also showed that the majority are just ‘believe' they can use technology in doing their job, but not integrating the technology expertise into their learning/teaching process. The recommendations for this study are also included for further research and use.